2017
DOI: 10.1371/journal.ppat.1006725
|View full text |Cite
|
Sign up to set email alerts
|

LipL21 lipoprotein binding to peptidoglycan enables Leptospira interrogans to escape NOD1 and NOD2 recognition

Abstract: Leptospirosis is a widespread zoonosis, potentially severe in humans, caused by spirochetal bacteria, Leptospira interrogans (L. interrogans). Host defense mechanisms involved in leptospirosis are poorly understood. Recognition of lipopolysaccharide (LPS) and lipoproteins by Toll-Like Receptors (TLR)4 and TLR2 is crucial for clearance of leptospires in mice, yet the role of Nucleotide Oligomerization Domain (NOD)-like receptors (NOD)1 and NOD2, recognizing peptidoglycan (PG) fragments has not previously been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 56 publications
7
54
0
1
Order By: Relevance
“…1). This protective role of LipL21 seems to be unique to Leptospira spp., since comparison of sequences did not show homology of LipL21 with any other bacterial protein [43]. In addition, we also found a peculiarity of the leptospiral PG composition that influences the species recognition by the NOD1 receptor.…”
Section: Toll-like Receptor (Tlr) and Nod-like Receptor (Nlr) Speciesmentioning
confidence: 66%
See 1 more Smart Citation
“…1). This protective role of LipL21 seems to be unique to Leptospira spp., since comparison of sequences did not show homology of LipL21 with any other bacterial protein [43]. In addition, we also found a peculiarity of the leptospiral PG composition that influences the species recognition by the NOD1 receptor.…”
Section: Toll-like Receptor (Tlr) and Nod-like Receptor (Nlr) Speciesmentioning
confidence: 66%
“…Our recent work showed that L. interrogans escape recognition by the cytosolic innate NOD1 and NOD2 receptors, which recognize peptidoglycan fragments called muropeptides [43]. Indeed, we showed that these receptors are not important for the clearance of L. interrogans in mice.…”
Section: Toll-like Receptor (Tlr) and Nod-like Receptor (Nlr) Speciesmentioning
confidence: 72%
“…In the case of L. interrogans , over 170 putative lipoproteins have been described, but their function remains mostly undetermined. We showed that LipL21 contributes to the escape of the immune system via very tight binding to peptidoglycan (PG) that required 4 hours boiling in SDS to be detached from the PG [33], hence preventing its recognition by the PRRs of the NOD family NOD1 and NOD2 [33]. Therefore, L. interrogans in which the abundance and variety of the lipoproteins is unusual, allowed us to highlight once more a potential new role for bacterial lipoproteins in innate immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Even though most of the functions of these lipoproteins remain a mystery, previous publications showed that some leptospiral lipoproteins play a role in the innate immune escape. Indeed, LipL21 binds tightly to the leptospiral peptidoglycan and hence prevents its recognition by the PRRs NOD1 and NOD2 [33]. Additionally, LipL21 and other lipoproteins have also been described as inhibitors of neutrophil myeloperoxidase [34].…”
Section: Introductionmentioning
confidence: 99%
“…We are only at the infancy of understanding the complexity in kidney disease due to pathogenic Leptospira and the positive or detrimental role of pattern recognition receptors. Although some pattern recognition receptors such as TLR4 and NOD1 display some host species specificities and induce differential recognition of leptospires between mice and human [38,39] , availability of mouse models, including transgenic and humanized mice, will be instrumental to boost further research and decipher the pathophysiology of renal leptospirosis and the mechanisms of pathogenic leptospires to escape the innate immune defenses.…”
Section: Resultsmentioning
confidence: 99%